Indications and complications of blood transfusion - Alsomali, Dunya Y.; Ismail, Amr A.; Moussa, Hassan M.; Almataani, Abdulhadi F.; Thabit, Yaser Y.; Alghamdi, Mohammed S.; Andijani, Reem M.; Munajjim, Fahad F. Al; Alaidarous, Hussain A.; Alqahtani, Turky A.; Aljurbui, Nasser J. (International Journal Of Community Medicine And Public Health, 2022)
Blood transfusion is a common procedure in the realm of medicine and surgery to treat hematological disorders such as iron and hemoglobin deficiency, during and after major surgical or invasive procedures, and in the event of trauma. However, this life saving procedure does not come without adverse complications and risks. In this review we will extensively discuss the indications of blood transfusion and the complications associated with blood transfusion. An extensive literature search was conducted in online databases such as PubMed, Google Scholar to include various publications such as narrative reviews, editorials and clinical practice guidelines on the indications of blood transfusion and its associated complications. After numerous large scale clinical trials and studies, the transfusion trigger for hemoglobin has been readjusted to a lower threshold thus preventing excessive transfusions and thereby limiting complications. There are a wide range of complications and adverse events associated with blood transfusions. Non-infectious transfusion reactions can contribute to significant morbidity and mortality and occur more commonly as compared to infectious transfusion reactions. Non-infectious reactions can be immune mediated and non-immune mediated and can also be subdivided based on their timing and occurrence after transfusion as acute occurring within 24 hours of transfusion and delayed as occurring 24 hours after transfusion. Further studies are warranted to create more precision on indications of blood transfusion especially for blood components such as platelets, fresh frozen plasma and cryoprecipitate are still undefined and need further trials to set cut-off limits to indicate transfusion.